Vision-Related Quality of Life and Its Sociodemographic Correlates Among Individuals With Visual Impairments. (July 2021) - Panigrahi, Ansuman; Nageswar Rao, G.; Kumari Konar, Amrita
Introduction: Visual impairment is an important public health concern worldwide that negatively affects quality of life (QOL). We aimed to assess the vision-related QOL and determine its sociodemographic correlates among individuals with visual impairments.Methods : We carried out a cross-sectional study during the years 2016–2017 among 201 individuals with visual impairments aged ≥ 40 years. After obtaining informed consent, we collected relevant information regarding sociodemographic characteristics using a pretested questionnaire and assessed vision-related QOL using the National Eye Institute Visual Function Questionnaire (VFQ-25). An ophthalmologist conducted comprehensive ophthalmic examinations of all the eligible study participants.Results: The mean VFQ-25 composite score was 52.91+ 7.61. The subscale score was highest for color vision (72.39+ 21.71) and worst in the dependency subscale (31.43+ 25.2). Multivariable ordinal regression revealed that variables such as gender, place of residence, household overcrowding, dietary habits, practicing exercise or yoga, and type of eye disorder were significantly ( p < .05) associated with the QOL of individuals with visual impairments.Discussion: The QOL among individuals with visual impairments was poor in our study. Further research is needed to establish associations of various factors with the QOL.Implications for practitioners: Incorporating these determinants of vision-related QOL in the existing strategies could be useful for health care providers and social service providers in promoting the well-being of individuals with visual impairments.